Long-Term Clinical Outcome and Prognosis After Thrombectomy in Patients With Concomitant Malignancy - Oki, Sogo; Kawabori, Masahito; Echizenya, Sumire; Shimoda, Yusuke; Shimbo, Daisuke; Osanai, Toshiya; Uchida, Kazuki; Houkin, Kiyohiro (Frontiers in Neurology, 2020)
Endovascular thrombectomy (EVT) is the preferred treatment strategy for patients with acute ischemic stroke (AIS). However, clinical outcome and prognosis in patients who undergo EVT in response to AIS with concomitant malignancy have not been fully elucidated. Data of patients with malignancy who underwent EVT at participating institutions between January 2015 and April 2019 were retrospectively analyzed. Patient characteristics, treatment methods, posttreatment strategy, and long-term prognosis were evaluated in 12 patients with prediagnoses of malignancy. Good revascularization (TICI 2b or higher) was achieved in 10 of 12 patients. Among the eight patients who survived more than 2 weeks from onset, four patients showed good clinical outcome [modified Rankin Scale (mRS) <2] at 60 days posttreatment and were able to continue treatment for malignancy. However, seven of eight patients died within a year of EVT (median survival, 83 days) due to progression of malignancy. One-year survival was achieved in only one patient whose etiology of stroke was determined as infectious endocarditis and not Trousseau syndrome. Even after successful revascularization and good short-term clinical outcome, the long-term prognosis after thrombectomy in patients with malignancy was poor. Thrombectomy for concomitant malignancy requires judicious decision, and further studies are necessary to fully elucidate its efficacy.